2020
DOI: 10.1111/all.14177
|View full text |Cite
|
Sign up to set email alerts
|

The need for clean air: The way air pollution and climate change affect allergic rhinitis and asthma

Abstract: Air pollution and climate change have a significant impact on human health and well‐being and contribute to the onset and aggravation of allergic rhinitis and asthma among other chronic respiratory diseases. In Westernized countries, households have experienced a process of increasing insulation and individuals tend to spend most of their time indoors. These sequelae implicate a high exposure to indoor allergens (house dust mites, pets, molds, etc), tobacco smoke, and other pollutants, which have an impact on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
193
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(241 citation statements)
references
References 171 publications
(417 reference statements)
5
193
0
8
Order By: Relevance
“…2 Experimental works and clinical evidence have shown that airborne pollutants can interact with pollen so as to exacerbate these conditions. 2,7 Such interactions, mainly with outdoor allergens, can occur through several mechanisms that have been only partially elucidated:…”
Section: The Impact Of Lockdown On Allergic Rhinitis: What Is Good Anmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Experimental works and clinical evidence have shown that airborne pollutants can interact with pollen so as to exacerbate these conditions. 2,7 Such interactions, mainly with outdoor allergens, can occur through several mechanisms that have been only partially elucidated:…”
Section: The Impact Of Lockdown On Allergic Rhinitis: What Is Good Anmentioning
confidence: 99%
“…[2][3][4] Overall, the environmental pollution may worsen allergic response by increasing the allergenicity of outdoor pollen and by promoting nonspecific airway inflammation. 2,7 Based on these highlights, we believe that we are having an invaluable opportunity to understand how human activities can affect both air and life quality in the allergic population. As previously stated, AR and asthmatic patients are supposed to benefit from the reduction of F I G U R E 1 These images, using data from the Copernicus Sentinel-5P satellite, show the average nitrogen dioxide concentrations, above Italy, from March 14 to 25, 2020, compared to the monthly average concentrations from 2019.…”
Section: The Impact Of Lockdown On Allergic Rhinitis: What Is Good Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Defects in innate immune responses, including neutropenia, alveolar macrophage dysfunction, and mutations in STAT3 (resulting in autosomal dominant hyper IgE syndrome) and impaired NAPDH oxidase activity facilitate the development of pulmonary, and in some cases invasive, aspergillosis (8), whereas mutations in the gene for CARD9 (signaling adaptor protein for the C-type lectin receptor) results in increased susceptibility to many types of fungal infection, including dermatophytosis (9,10). The reasons for the increased incidence of fungal infections over recent decades are beyond the scope of this manuscript and readers are directed to several excellent reviews on the subject (3,4,7,(11)(12)(13)(14)(15). Fungi are ubiquitous throughout nature and we are constantly exposed to these microbes from the environment via inhalation, ingestion or on epithelial surfaces including the skin and mucosae (16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…4,[6][7][8][11][12][13][14][15][16][17][18][19][20] Recent studies have revealed that environmental exposures, global warming, and climate change have negative effects on respiratory health and increase the allergenicity of some allergens. [21][22][23][24][25] A systematic review and metaanalysis has reported that exposure to cleaning products is associated with an increased risk of asthma. 26 Many epidemiologic and surveillance studies, and several case reports, have identified an association between increased risk of asthma and exposure to cleaning sprays, bleach, ammonia, disinfectants, mixing products, as well as specific works exposed to asthmainducing triggers.…”
mentioning
confidence: 99%